THE UNUSUAL SECRETS OF QUANTUM PHYSICS - Berkinov Alisher Abdurashidovich (Bright Mind Publishing, 2025)
This article focuses on the fundamental principles of quantum physics and their unusual mysteries. Concepts such as Dual nature, superposition state, quantum entanglement and tunneling are of great importance not only in the development of modern technologies, but also in expanding the perception of human thought and the universe. The article philosophically and scientifically covers the unconventional phenomena of the quantum world, reflecting on the impact of this field on human life and technologies that can be created in the future.
Keywords: Quantum physics, superposition, observational phenomenon, quantum entanglement, quantum tunneling, uncertainty principle, quantum causality, quantum teleportation, Universe and quantum fluctuations, human brain and quantum mechanics.